2006
DOI: 10.1590/s0101-31222006000200024
|View full text |Cite
|
Sign up to set email alerts
|

Sistema hidropônico com uso de solução de herbicida na detecção de soja geneticamente modificada resistente ao glifosato

Abstract: -The objectives of this work were to verify the efficiency of the hydroponic system in the detection of genetically modified (GM) soybean seeds and to establish a detection protocol in the hydroponic system. Seed samples of the two genotype were used, one genetically modified and the respective non-genetically modified (non-GM) parent. Five assays were performed to establish the detection protocol, in assays I and II the seed pre-germination was performed and later the seedlings were placed in recipients conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
2
Order By: Relevance
“…Novamente esse efeito nas plântulas é atribuído à ação inibitória do herbicida que provoca o déficit de aminoácidos aromáticos e compostos fenólicos secundários, afetando a organogênese, e retardando e/ou paralisando a diferenciação das raízes (Bervald et al, 2010). Concordando com os resultados obtidos, alguns autores observaram que a ação do glifosato reduz o comprimento das plântulas, parte aérea e raiz, além de inibir a emissão de raízes secundárias dos genótipos de soja convencionais, sendo que a ausência dessas raízes foi utilizada como um dos principais parâmetros na diferenciação de plântulas dos genótipos suscetíveis e resistentes ao herbicida (Tillmann & West, 2004;Bertagnolli et al, 2006;Funguetto et al, 2004). Rebessi et al (2011), avaliando a toxicidade do herbicida glifosato em sementes de milho, também observaram efeito deletério dele em quase todas as doses utilizadas, com redução efetiva na germinação e no desenvolvimento das radículas, como constatado neste estudo.…”
Section: Londrina-pr 2014unclassified
“…Novamente esse efeito nas plântulas é atribuído à ação inibitória do herbicida que provoca o déficit de aminoácidos aromáticos e compostos fenólicos secundários, afetando a organogênese, e retardando e/ou paralisando a diferenciação das raízes (Bervald et al, 2010). Concordando com os resultados obtidos, alguns autores observaram que a ação do glifosato reduz o comprimento das plântulas, parte aérea e raiz, além de inibir a emissão de raízes secundárias dos genótipos de soja convencionais, sendo que a ausência dessas raízes foi utilizada como um dos principais parâmetros na diferenciação de plântulas dos genótipos suscetíveis e resistentes ao herbicida (Tillmann & West, 2004;Bertagnolli et al, 2006;Funguetto et al, 2004). Rebessi et al (2011), avaliando a toxicidade do herbicida glifosato em sementes de milho, também observaram efeito deletério dele em quase todas as doses utilizadas, com redução efetiva na germinação e no desenvolvimento das radículas, como constatado neste estudo.…”
Section: Londrina-pr 2014unclassified
“…No que se refere à soja GM tolerante ao glifosato, bioensaios com diferentes princípios vêm sendo publicados no intuito de fornecer uma metodologia confiável para detecção de sementes de soja GM em lotes de sementes de soja não-GM. Entre os bioensaios, todos com bons resultados, podem ser citados: germinação seguida de aplicação do herbicida sobre as plantas (Goggi and Stahr, 1997); pulverização foliar com glifosato pós-germinação (Bevilaqua et al, 2000;Torres et al, 2003); umedecimento do substrato de germinação com solução do herbicida (Bevilaqua et al, 2000;Funguetto et al, 2004;Miranda et al, 2005); identificação com base na atividade de enzimas (Menezes et al, 2004); imersão de sementes em solução do herbicida (Funguetto et al, 2004;Tillmann and West, 2004); pré-embebição de sementes em substrato umedecido com glifosato (Goggi and Stahr, 1997;Funguetto et al, 2004;Tillmann and West, 2004); emergência da plântula em areia, seguida de aplicação do herbicida (Miranda et al, 2006); e, detecção em sistema hidropônico (Bertagnolli et al, 2006).…”
Section: Introductionunclassified
“…Glyphosate causes abnormalities on NGM soybean seedlings, causing formations of tapered, smooth, and firm roots, besides reduction on length of primary root and aerial parts of the plant, and inhibition of secondary roots emission; while the GM soybean seedlings display primary root and aerial parts well developed and abundant, when treated with the herbicide (Bertagnolli et al, 2006). Cultivars GM have the gene for resistance to glyphosate, thus allowing formation and development of normal seedlings; and for this reason, the soybean seedlings originating from GM seeds remain unchanged after treatment with glyphosate, contrasting with death, or growth reduction, of seedlings observed in treatment of conventional soybean with glyphosate, to which it is sensitive (Padgette et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Using hydroponic system with herbicide solution, Bertagnolli et al (2006) have found that this system allows detecting soybean seeds of glyphosate resistant cultivars in only five days; and Miranda et al (2006), in a bioassays conducted under greenhouse conditions, have sown soybean seeds on a sand substrate, and after germination, they have treated the seedlings with solution of herbicide glyphosate, verifying that the treatment was efficient, practical and of easy conduction.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation